Article retraction notice - Uredništvo (Vojnosanitetski Pregled)
(retraction) The article 'Prognostic significance of acute bundle branch block in patients with acute myocardial infarction' by Mijailović V, Mrdović I, Ilić M, Ašanin M, Srdić M, Rajić D was retracted at the request of the editors because the authors had infringed the normal professional and ethical codes by submitting the above article to the Vojnosnitetski pregled after an article with substantial overlap of its content (patients, methods,results and conclusions) had been accepted for publication and published in another journal, ABC - časopis urgentne medicine. (1) Mijailović V, Mrdović I, Ilić M, Ašanin M, Srdić M, Rajić D. 'Prognostic significance of acute bundle branch block in patients with acute myocardial infarction' Vojnosanit Pregl 2008; 65(10): 733-7. (Serbian) (2) Mijailović V, Mrdović I, Ilić M, Peruničić J, Ašanin M, Lasica R, Savić L, Srdić M, Jozić T, Rajić D, Terzić B, Matić D, Matić M, Vasiljević Z. 'Prognostic significance of acute bundle branch block with patients suffering from myocardial infarction'. ABC - časopis urgentne medicine 2007; 7(2-3): 104-8. (Serbian) . Link to the retracted article 10.2298/VSP0810733M